2012
DOI: 10.1007/s10519-012-9533-2
|View full text |Cite
|
Sign up to set email alerts
|

Aggression, Digit Ratio, and Variation in the Androgen Receptor, Serotonin Transporter, and Dopamine D4 Receptor Genes in African Foragers: The Hadza

Abstract: The role of genes in the expression of aggression and masculinity traits in humans has been a focus of recent behavioral genetic studies. This is the first study on the variation in aggression, the digit ratio (the ratio between the second and the fourth digits, 2D:4D), the directional asymmetry in 2D:4D (D(R-L)) and polymorphisms of the AR, DRD4, and 5-HTTL genes in simple hunter-gatherers, namely the Hadza of Tanzania (142 adult men). The distribution of AR, DRD4E3, and 5-HTTLPR genotypes and allele frequenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
55
2
9

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(71 citation statements)
references
References 116 publications
5
55
2
9
Order By: Relevance
“…The association between the lower number of CAG-repeats in AR gene and masculinity, particular with the lower digit ratio (2D:4D) in men from the population of the Hadza (traditional East African huntergatherers) had been recently found [9]. Also, the data from China have indicated that AR CAG repeat polymorphism was associated with the exercise performance after simulated normobaric hypoxic training in North China Han men, and that the shorter genotypes (21 repeats and lower) had a better individual response to hypoxic training, compared to the carries of longer variants (22 repeats and longer) [21].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The association between the lower number of CAG-repeats in AR gene and masculinity, particular with the lower digit ratio (2D:4D) in men from the population of the Hadza (traditional East African huntergatherers) had been recently found [9]. Also, the data from China have indicated that AR CAG repeat polymorphism was associated with the exercise performance after simulated normobaric hypoxic training in North China Han men, and that the shorter genotypes (21 repeats and lower) had a better individual response to hypoxic training, compared to the carries of longer variants (22 repeats and longer) [21].…”
Section: Resultsmentioning
confidence: 99%
“…Obviously, environmental factors such as training, parental support play an important role in successful sportive career, but as mentioned above genetic factors do matter. Ten polymorphisms selected for analysis in this study are connected to the functioning of serotonergic, dopaminergic and androgenic systems according to other studies presumably may be associated with resistance to psychological stress, emotional control, competitiveness and aggression [6][7][8][9]13,19,37]. Although the sample size in this study was quite low it is still possible to suggest that functionally important polymorphisms of genes in serotonergic system provide some evidence of strong selective pressure in direction of genotypes associated with low level of free serotonin in successful judo athletes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations